Jesus Christ message to all nations - Jeffs, Warren, 1955- (Fundamentalist Church of Jesus Christ of Latter Day Saints, 2012)
Un compendio de las profecías atribuídas a Jesucristo por Warren S. Jeffs entre 2010-2012, principalmente en Palestina, Texas